Less is more: Limited fractionation yields stronger gels for pea proteins. (March 2021) - Kornet, Remco; Veenemans, Justus; Venema, Paul; van der Goot, Atze Jan; Meinders, Marcel; Sagis, Leonard; van der Linden, Erik
Abstract: Limited fractionation of yellow pea yielded functional protein fractions with higher gelling capacity. Pea protein concentrates were obtained by dispersing flour at unadjusted pH ( 6.7) and at pH 8. An additional isoelectric precipitation step resulted in a protein-rich isolate and a protein-poor supernatant. Aqueous solutions of these pea fractions (up to 15 wt %) were heated from 20 to 95 and subsequently cooled to 20 °C, and their viscoelastic response was characterized by small and large amplitude oscillatory shear measurements (SAOS and LAOS, respectively). SAOS rheology showed that the limited fractionated protein concentrates formed significantly firmer gels per mass of protein after cooling, than the more extensively fractionated protein isolate, with elastic moduli of G' 10 3 Pa and G' 10 2 Pa, respectively. LAOS rheology showed an overall strain softening behaviour for all pea fractions and a transition from elastic to viscous behaviour at smaller strain for the protein isolate. Confocal and electron microscopic images were consistent with those observations, and revealed a more homogeneous network for the limited fractionated samples, and a more heterogenous network for the protein isolate. A number of experiments showed that there are different processing and compositional factors affecting gelling capacity. These are isoelectric precipitation, amount of sugars upon lyophilization and differences in ash content. Furthermore, differences in pre-aggregated state, as found in earlier research, may be partially responsible for the different gelling behaviour. In conclusion, we explain how fractionation affects pea proteins and found that limited fractionation yields pea proteins that form stronger gels. Graphical abstract: Image 1 Highlights: Limited fractionation yields pea protein concentrates with a higher gel firmness per mass of protein. Those gels also show a later transition from elastic to viscous behaviour upon large deformation. Extensively fractionated pea protein formed a more heterogeneous gel network with protein dense regions. Factors responsible for a reduced gel firmness are isoelectric precipitation, ionic strength and sugars upon lyophilization.